Paternal preconceptional supplementation of n‐3 polyunsaturated fatty acids alleviates offspring nonalcoholic fatty liver disease in high‐fat diet‐induced obese mice - Qiaoyu Shi; Xiuqin Fan; Mengyi Yang; Tiantian Tang; Rui Wang; Ping Li; Kemin Qi (Food Frontiers, 2024)
Abstract Exposure to nutritional or environmental factors in early life determines susceptibility to nonalcoholic fatty liver disease (NAFLD). The effect of paternal preconceptional n‐3 polyunsaturated fatty acids (n‐3 PUFAs) on offspring NAFLD development remains unknown. Herein, a mouse model that weaning male mice (F0) received diet supplementation of normal n‐3 PUFA content (n‐6:n‐3 PUFA ratio = 4.3:1) or high n‐3 PUFA content (n‐6:n‐3 ratio = 1.5:1) for 12 weeks, and an n‐3 PUFA‐deficient diet as control, was used for the production of next generation. The F1 and F2 offspring were generated by mating F0 and F1 male mice with virgin female mice, respectively, and after weaning, were fed a high‐fat diet to induce NAFLD. The paternal n‐3 PUFA supplementation improved the scores of steatosis, inflammation and ballooning, and the fibrosis in the liver of two generations, with expressional upregulation of genes associated with fat oxidation (Atgl, Ppara, or Cpt1a), and downregulation of inflammatory genes (Ccl2, Tnf‐α, F4/80, CD206, or CD11c) and fibrosis genes (Tgf‐β, Timp1, or Col1a1). The lessened brown adipose tissue whitening, altered gut bacterial compositions, and altered expression of the imprinted genes (H19, Igf2, and Plagl1) might mediate the impact of paternal n‐3 PUFAs on offspring's NAFLD development, which was dose‐dependent. The data indicate that preconceptional higher paternal intake of n‐3 PUFAs might have intergenerational and transgenerational alleviating impact on obesity‐associated NAFLD development in the offspring through multiple pathways.